The Roles of International Law on Technological Advances - Latifah, Emmy; Imanullah, Moch Najib (Brawijaya Law Journal, 2018)
The study focuses on the roles of International Law in responding to the technological advances, particularly examining the International Law as a regulator on emerging technology. The technological advances, especially in the means and method of war and environmental issues, have been contributing to the development of International Law. It is a normative legal research using the secondary data including primary and secondary legal materials. While the primary legal materials consist of all the international agreement related to the development of technology both directly and indirectly, secondary ones included the references having correlation and support to the issues. The technique of analysis data used legal interpretation. The study concludes that as a regulator of technological advances, International Law has a role to play in regulating its development. Many facts showed that International Law has capability to respond to the challenges. However, the scope and application of International Law is subject to a number of limitations inherent the nature of International Law itself.